Respuesta :

Answer:

[tex]\dfrac{dy}{dx}=\dfrac{y^2-2 \sin(x)}{1-2xy}[/tex]

Step-by-step explanation:

Given equation:

[tex]y=y^2x+2 \cos(x)[/tex]

To find the derivative of the given equation, use implicit differentiation.

Add d/dx in front of each term:

[tex]\dfrac{d}{dx}\:y =\dfrac{d}{dx}\:y^2x+\dfrac{d}{dx}\:2 \cos(x)[/tex]

Differentiate terms in x only (and constant terms) with respect to x:

[tex]\dfrac{d}{dx}\:y =\dfrac{d}{dx}\:y^2x-2 \sin(x)[/tex]

Use the chain rule to differentiate terms in y only:

(in practice this means to differentiate with respect to y then place dy/dx on the end)

[tex]\dfrac{dy}{dx}\: =\dfrac{d}{dx}\:y^2x-2 \sin(x)[/tex]

Use the product rule on the term in x and y:

[tex]\textsf{let }u=y^2 \implies \dfrac{du}{dx}=2y \dfrac{dy}{dx}[/tex]

[tex]\textsf{let }v=x \implies \dfrac{dv}{dx}=1[/tex]

[tex]\implies u\dfrac{dv}{dx}+v\dfrac{du}{dx}=y^2+2xy \dfrac{dy}{dx}[/tex]

Therefore:

[tex]\dfrac{dy}{dx} =y^2+2xy \dfrac{dy}{dx}-2 \sin(x)[/tex]

Rearrange to make dy/dx the subject:

[tex]\dfrac{dy}{dx}-2xy \dfrac{dy}{dx} =y^2-2 \sin(x)[/tex]

[tex]\dfrac{dy}{dx}(1-2xy)=y^2-2 \sin(x)[/tex]

[tex]\dfrac{dy}{dx}=\dfrac{y^2-2 \sin(x)}{1-2xy}[/tex]

ACCESS MORE